Towards a uniform legal system of protection - Chotouras, D (Refugee Studies Centre, University of Oxford, 2012)
There exists a set of inter-related normative texts for the protection of the environment and for the prevention and reduction of disasters, as well as for ensuring respect for human rights in all circumstances. Taken together these standards constitute an effective legal and operational framework and should not be interpreted independently or in isolation.